The role of Hajjaj bin Yusuf Al - Thaqafi in the linguistic reform of the Holy Quran (Journal of the College of Education for Women, 2018)
During his tenure in Iraq, al-Hadjjaj bin Yusif undertook administrative and economic reforms as well as linguistic reform.The efforts exerted by Abu al-Aswad al-Dawali to control the reading of the Holy Quran were not sufficient, so the melody and error continued and became more pronounced, especially since the letters were written until then without any distinguishing features.Al- Hadjjaj bin Yusuf realized the seriousness of the continuation of these errors and what he talked with the days of the causes of division and disagreement between the Muslim community ordered his book to put these suspicious characters marks was at the head of the book Nasr bin Asim and Yehi bin Muammar